Student Perceptions of the Learning Effectiveness of Printed Versus Digital Textbooks in College Accounting Classes - Pamela Elaine Baker (Journal of Accounting, Business and Management (JABM), 2022)
Previous studies queried the use of e-texts with regard to creating stress and understanding. This study adds to the literature as it investigates college student perceptions of the usefulness of e-texts versus printed texts in learning accounting. Undergraduate and graduate accounting students in online, hybrid, and face-to-face courses with access to e-texts, in-print text purchases, and in-print text rentals at two postsecondary institutions in North Texas answered questions about whether using e-texts or printed texts better aided them in learning accounting. Results indicate that a vast majority of those surveyed report better learning with the use of a purchased, printed text.